LYMPHOCYTE APOPTOSIS IN PSORIASIS - О. M. Kapuler; Е. V. Nelyubin; D. A. Kaut; S. V. Sibiryak (Медицинская иммунология, 2014)
Abstract. Forty-two patients with progressive vulgar psoriasis (PASI = 19.7 ± 1.5) and 40 healthy volunteers were under investigation. Psoriatic patients were characterized by increased number of CD4+ CD95+ peripheral blood T lymphocytes, which correlates with clinical psoriatic score, and by increased levels of soluble Fas (sFas) in serum, as compared to controls (resp., 1868.1 ± 186.8 pg/ml vs. 1281.4 ± 142.5 pg/ml, PLSD = 0.019). The levels of spontaneous lymphocyte apoptosis and anti-Fas (Mab)-induced apoptosis in psoriatic patients did not differ from the controls. However, apoptosis induced by “oxidative stress” (50 M Н202, 4 hrs) was depressed in the patients. Moreover, a simultaneous assessment of cell cycle structure (metachromatic staining with Acridine Orange), apoptosis and Fas receptor expression (AnnV-FITC/antiFas mAbs-PE staining) following a short-term mitogenic stimulation (PHA-P, 5 µg/ml, 24 hrs) were performed. We found no marked differences in mitogenic reactivity, activation-induced apoptosis, and activation-induced Fas receptor expression when studying lymphocytes from healthy donors and psoriatic patients. However, PHA-activated lymphocytes from psoriatic patients displayed a significantly decreased ratio of AnnV+CD95+ to the total AnnV+ subpopulation, thus suggesting a decreased role of Fas-dependent mechanisms of apoptosis during the cell activation. The data obtained confirm a view, that an abnormal lymphocyte “apoptotic reactivity”, which plays a crucial role in the mechanisms of autoimmunity, may also of importance in the pathogenesis of psoriasis.